Practice Guidelines for Management of Migraine - J Gordon Millichap (Pediatric Neurology Briefs)
The literature (166 articles identified and reviewed) on the pharmacological treatment of the child with migraine headache was classified according to acute headache and preventive medications, and the results of drug trials were evaluated by Committees of the Child Neurology Society and American Academy of Neurology.